Glucosylated forms of serotonin and tryptophan in green coffee beans. (November 2016) - Servillo, Luigi; Giovane, Alfonso; Casale, Rosario; Cautela, Domenico; D'Onofrio, Nunzia; Balestrieri, Maria Luisa; Castaldo, Domenico
Abstract: Green beans of Robusta and Arabica coffee species were examined by HPLC-ESI-MS 2 analysis for the content of glycosylated forms of serotonin and its N- methylated derivatives. The results showed for the first time the occurrence of serotonin 5- O - β -glucoside and tryptophan- N 1 -glucoside in coffee beans. Both substances were identified by their product ion spectra and by comparison with synthesized authentic standards. Interestingly, serotonin 5- O - β -glucoside occurs at similar levels in beans of all varieties of Robusta and Arabica coffee species, whereas tryptophan- N 1 -glucoside is present at high levels in beans of Robusta and at much lower levels in those of Arabica species. This striking difference in the content of tryptophan- N 1 -glucoside could afford a new tool to discriminate between beans of Arabica and Robusta coffee species. Highlights: Serotonin 5- O -β-glucoside was detected for the first time in coffee beans. Tryptophan-N1-glucoside was detected for the first time in coffee beans. The mass spectrometric features of the above compounds were reported. Tryptophan-N1-glucoside was much more abundant in Robusta than in Arabica seeds. The above result affords a tool to differentiate Robusta and Arabica seeds.